2017
DOI: 10.4103/0972-9941.199606
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity analysis in minimally invasive esophagectomy for oesophageal cancer versus conventional over the last 10 years, a single institution experience

Abstract: BACKGROUND:There has been an increasing inclination towards minimally invasive esophagectomies (MIEs) at our institute recently for resectable oesophageal cancer.OBJECTIVES:The purpose of the present study is to report peri-operative and long-term procedure specific outcomes of the two groups and analyse their changing pattern at our institute.METHODS:All adult patients with a diagnosis of oesophageal cancer managed at our institute from 2005 to 2015 were included in this retrospective study. Patients’ demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The review identified 98 studies 6,7,34–129 comparing surgical approaches for oesophagectomy, involving 32 315 patients ( Fig . 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review identified 98 studies 6,7,34–129 comparing surgical approaches for oesophagectomy, involving 32 315 patients ( Fig . 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Khan et al study pulmonary complication rate was 28.4%. 17 In other studies pulmonary complications ranges from 5% to 36% as mentioned in Table 4. In present study anastomotic leak was seen in 4 (20) patients which was managed conservatively.…”
Section: Discussionmentioning
confidence: 86%
“…In present study overall mortality rate was 5% whereas in braghetto et al study it was 2.8% and 2.1% in Khan et al study. 17,18 In other studies it ranges from 0% to 4.5% as mentioned in Table 4.…”
Section: Discussionmentioning
confidence: 90%
“…To date, a number of studies have demonstrated acceptable short‐term outcomes of MIE in terms of operating time, blood loss and postoperative complications. Some studies have demonstrated that the incidence of respiratory complications was significantly lower with MIE than that with open esophagectomy (OE) . Straatman et al .…”
Section: Discussionmentioning
confidence: 99%